The digital era: will you trust me? / Norhidayah Ali ... [et al.] - Ali, Norhidayah; Mohamed Isa, Zuraidah; Ibrahim, Dahlia (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The trend of going online demonstrates a tremendous increase among companies. The increase is attributed to the change in consumer behavior and the pandemic. Companies that originally employ brick-and-mortar as their sole distribution channel are now venturing into the digital platform. Various companies are shutting down their brick-and-mortar outlets and are focusing on the online platform exclusively. This move highlights that companies who are still perform their business the traditional way might lose their business or sales decline.